Some problems of expert estimations of approbation results of civil aviation normative and guiding documentation - Мелкумян, В. Г.; Семенов, А. А. (Proceedings of National Aviation University (archive), 1999)
Considered are peculiarities of working out civil aviation normative and guiding documentation. Presented is one of approaches to experimental estimation of approbation results of normative guiding documentation using applied section of theory of odd sets